Utilizing Chimeric Antigen Receptors to Direct Natural Killer Cell Activity - Hermanson, David L.; Kaufman, Dan S. (Frontiers in Immunology, 2015)
Natural killer (NK) cells represent an attractive lymphocyte population for cancer immunotherapy due to their ability to lyse tumor targets without prior sensitization and without need for HLA-matching. Chimeric antigen receptors (CARs) are able to enhance lymphocyte targeting and activation towards diverse malignancies. CARs consist of an external recognition domain (typically a small chain variable fragment) directed at a specific tumor antigen that is linked with one or more intracellular signaling domains that mediate lymphocyte activation. Most CAR studies have focused on their expression in T cells. However, use of CARs in NK cells is starting to gain traction because they provide a method to redirect these cells more specifically to target refractory cancers. CAR-mediated anti-tumor activity has been demonstrated using NK cell lines, as well as NK cells isolated from peripheral blood, and NK cells produced from human pluripotent stem cells. This review with outline the CAR constructs that have been reported in NK cells with a focus on comparing the use of different signaling domains in combination with other co-activating domains.